2019
DOI: 10.1016/s1474-4422(19)30043-2
|View full text |Cite
|
Sign up to set email alerts
|

Stroke genetics: discovery, biology, and clinical applications

Abstract: Stroke, a leading cause of long-term disability and death worldwide, has a heritable component. Recent gene discovery efforts have expanded the number of known single-gene disorders associated with stroke and linked common variants at approximately 35 genetic loci to stroke risk. These discoveries have highlighted novel mechanisms and pathways implicated in stroke related to large artery atherosclerosis, cardioembolism, and small vessel disease, and defined shared genetic influences with related vascular trait… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
123
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 149 publications
(146 citation statements)
references
References 103 publications
2
123
0
5
Order By: Relevance
“…37 Fourth, we found that assessment of PRS and biochemistry markers could improve prediction of CHD outcomes much more than they improve prediction of stroke outcomes. Reasons for such differential gains may relate to both the greater phenotypic heterogeneity of stroke outcomes, [38][39][40] and the relatively lower statistical power of previous GWAS studies of stroke, 29 compared with CHD. 28,40 Nevertheless, to reflect current guidelines and practice in CVD prevention, the primary outcome of our study was any first cardiovascular event (defined as fatal or nonfatal CHD or stroke).…”
Section: Discussionmentioning
confidence: 99%
“…37 Fourth, we found that assessment of PRS and biochemistry markers could improve prediction of CHD outcomes much more than they improve prediction of stroke outcomes. Reasons for such differential gains may relate to both the greater phenotypic heterogeneity of stroke outcomes, [38][39][40] and the relatively lower statistical power of previous GWAS studies of stroke, 29 compared with CHD. 28,40 Nevertheless, to reflect current guidelines and practice in CVD prevention, the primary outcome of our study was any first cardiovascular event (defined as fatal or nonfatal CHD or stroke).…”
Section: Discussionmentioning
confidence: 99%
“…The risk of ischaemic stroke is determined by a complex interplay of genetic and environmental factors partly acting through modifiable risk factors such as hypertension and diabetes. Roughly thirty-five genomic loci have been robustly associated with stroke [4][5][6][7] , and many more genetic associations have been reported for stroke-related risk factors [8][9][10][11][12][13][14] , e.g., over 1,000 loci have been associated with blood pressure (BP) 11,[15][16][17][18][19] and >100 with atrial fibrillation (AF) 10,20 . These data are now beginning to be harnessed to aid risk prediction.…”
Section: Introductionmentioning
confidence: 99%
“…For stroke, a recent 90-SNP GRS derived from the MEGASTROKE GWAS metaanalysis 4 showed that genetic and lifestyle factors are independently associated with incident stroke 24 , and that even among individuals with high GRS, lifestyle factors had a large impact on risk, implying that risk could be reduced in those with high genetic predisposition for stroke. However, in contrast to GRSs for other cardiovascular diseases like coronary artery disease (CAD) [21][22][23] , the predictive power of previous GRS for stroke has been limited [25][26][27] , likely because of limited genetic data for stroke and the well-known heterogeneity of the stroke phenotype 4,7 . Recent analytical advances have enabled more powerful GRS construction, such as those leveraging multiple sets of GWAS summary statistics 21,28 , potentially allowing for power and heterogeneity limitations to be overcome.…”
Section: Introductionmentioning
confidence: 99%
“…However, the underlying pathogenesis has not yet been fully understood. The substantial advance in the research of epigenetic modifications might provide new insights into this field and help understand additional pathological mechanisms (5,6). DNA methylation is one of the most understood epigenetic mechanisms (7).…”
Section: Introductionmentioning
confidence: 99%